2015
DOI: 10.1080/02699931.2014.1000830
|View full text |Cite
|
Sign up to set email alerts
|

Explicit vs. implicit emotional processing: The interaction between processing type and executive control

Abstract: The current study examined whether the interaction between emotion and executive control (EC) is modulated by the processing type of the emotional information. Namely, whether the emotional information is explicitly processed, implicitly processed or passively viewed. In each trial, a negative or neutral picture preceded an arrow-flanker stimulus that was congruent or incongruent. Incongruent stimuli are known to recruit EC. Explicit processing of the pictures (Experiment 1a), which required responding to thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
4
22
2
Order By: Relevance
“…No main effect of valence was observed in the current experiments, which is in contrast to many of the published results [26,38,44,50,62,68]. This sheds even more light on the role of arousal, as some recent studies already reported the lack of pure valence effects in the procedures requiring cognitive control, especially when arousal is orthogonally crossed with valence [56,60,61,63,64].…”
Section: Plos Onecontrasting
confidence: 99%
See 1 more Smart Citation
“…No main effect of valence was observed in the current experiments, which is in contrast to many of the published results [26,38,44,50,62,68]. This sheds even more light on the role of arousal, as some recent studies already reported the lack of pure valence effects in the procedures requiring cognitive control, especially when arousal is orthogonally crossed with valence [56,60,61,63,64].…”
Section: Plos Onecontrasting
confidence: 99%
“…In regards to the congruence between colours of flankers and the target word, we found that incongruent trials elicited longer responses in both of the procedures. This effect has the same shape as differences in reaction times between congruent and incongruent trials in the Stroop task [1,11,12,14,47,61] and flanker task [1,40,47,48,[62][63][64]. Observation of this effect confirms that the tasks employed for both of the experiments described in this study engaged cognitive control in a similar way, like the tasks that were the inspiration for developing these flanker-modified EST procedures.…”
Section: Discussionsupporting
confidence: 66%
“…It is thus possible that the intensity of emotion in our stimuli was too low to produce a pronounced valence modulation because we specifically controlled low-level visual properties across all face stimuli. Notably, research has shown differences between explicit and implicit emotional processing (5759), and weaker emotional modulation when the executive control is involved (60). Therefore, it is also possible that our explicit task requirement for emotion identification and valence and arousal rating automatically engaged the executive network, which greatly interrupted normal emotional face processing, resulting in weak emotional effects.…”
Section: Resultsmentioning
confidence: 99%
“…Implicit processing of emotional features occurs following presentation of face stimuli, even under conditions in which the emotional content is not task-relevant (e.g. Cohen et al, 2016). Thus, emotion decoding deficits may detract from processing capacity in non-affective (i.e.…”
Section: Discussionmentioning
confidence: 99%